11th Intelligent Systems for Molecular Biology 2003 (ISMB 2003). Issue 6 (2003) - Abbott, Catherine A.
Abstract : This report profiles the keynote talks given at ISMB03 in Brisbane, Australia by Ron Shamir, David Haussler, John Mattick, Yoshihide Hayashizaki, Sydney Brenner, the Overton Prize winner, Jim Kent, and the ISCB Senior Accomplishment Awardee, David Sankov.